Penggunaan Media Sosial di Rumah Sakit: A Systematic Review - Wijayati, Andini Tri; Habsari, Angesti Drea Habsari Drea; arinahaq, arinahaq; Kusumasari, Fiki; Selvia, Rosa; Iroth, Rovels Agber Maywell (UI Scholars Hub, 2020)
The progression of Internet access changes from passive consumer interaction becomes active consumer to seek health information. Social media not only a recreational instrument but also for business and organization. Initially, consumers obtained health information from websites that were one-way (only receiving information) but nowadays social media change consumer become two directions (receiving and spread information). This eligibility study was a systematic review with PRISMA (Preferring Reposting Items for Systematic Review and Meta-Analysis Protocols) approach. Conducted by searching articles from one database Science Direct and published from January 2014 to 2019. Searching and screening proces resulted in 5 articles to review from 700 articles related the use of social media in hospitals. The keywords used are social media, hospital, marketing. Over the past decade, user of social media outlets has grown exponentially. High enthusiasm patients were willing to to receive health related information and education from official source. Social media has a positive impact on improving knowledge, patient satisfaction, publication and also hospitals marketing